Disparate Changes in Plasma and Brainstem Cytokine Levels in Adult and Ageing Rats Associated with Age-Related Changes in Facial Motor Neuron Number, Snout Muscle Morphology, and Exploratory Behavior - Katharesan, Viythia; Lewis, Martin David; Vink, Robert; Johnson, Ian Paul (Frontiers in Neurology, 2016)
An overall increase in inflammatory cytokines with age in both the blood and the central nervous system (CNS) has been proposed to explain many aspects of ageing, including decreased motor function and neurodegeneration. This study tests the hypothesis that age-related increases in inflammatory cytokines in the blood and CNS lead to facial motoneurone degeneration. Groups of 3-5 female Sprague-Dawley rats aged 3 months, 12-18 months and 24 months were used. Twelve cytokines (IL-1α, IL-β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12p70, I L-13, TNFα, IFN-γ and GM-CSF.) were measured in blood plasma and compared with those in the brainstem after first flushing blood from its vessels. The open-field test was used to measure exploratory behaviour and the morphology of the peripheral target-muscle of facial motoneurones quantified. Total numbers of facial motoneurones were determined stereologically in separate groups of 3m and 24m rats. Ageing rats showed a significant 30-42% decrease in blood plasma (peripheral) concentrations of IL-12p70 and TNFα, and a significant 43-49% increase in brainstem (central) concentrations of IL-1α, IL-2, IL-4, IL-10 and TNFα. They also showed significant reductions in motoneurone number in the right but not left facial nucleus, reduced exploratory behaviour and increased in peripheral target muscle size. Marginal age-related facial motoneuronal loss occurs in the ageing rat and is characterised by complex changes in the inflammatory signature, rather than a general increase in inflammatory cytokines.